(untitled) (Comprehensive Journal of Science, 2026)
This study examines the impact of linguistic disagreement on jurisprudential choices, highlighting the close relationship between language and various fields of knowledge, as well as its role in generating diversity in opinions and interpretations. It demonstrates the strong connection between linguistic and jurisprudential views, particularly through grammatical disagreement, which is influenced by factors such as the level of linguistic competence. The study further explores the effect of linguistic disagreement on jurisprudential reasoning in the works of Makki al-Qaisi, showing how such disagreements shaped his legal preferences. It also reveals that his jurisprudential choices were largely influenced by the Basran school of grammar. Moreover, the study emphasizes the importance of linguistic knowledge and an understanding of grammatical differences in determining legal rulings. It highlights the need for further research into linguistic issues within foundational jurisprudential texts, especially in Maliki literature, which contains numerous instances of linguistic debate and the views of grammarians. These aspects require deeper study and systematic compilation, particularly given that many of these scholars belong to earlier periods.